Urinary excretion of N-Acetyl Glucosaminidase (NAG) as a marker of tubular injury in cyclosporin A associated nephrotoxicity in rat and human - Soliman, A R; Khalifa, M G; Ahmed, A T; El-Said, A M; Francis, M R; El Sersawy, G; Sharafeldin, U A (African Journal of Nephrology, 2023)
The possible role of NAG in the diagnosis of early reversible renal tubular damage caused by cyclosporin A (CyA) was examined. A trial was also done to elucidate any possible cmrelation in chronic CyA nephrotoxicity. We first tested the effects of different doses of Cy A (10,20,40, and 80 mg/kg) on urinary NAG level, serum creatinine (Cr), sodium (Na), potassium (K), creatinine clearance (CC), FENa, FEK, and histopathology of the rat kidney. Secondly, we determined blood CyA trough level in rat and human renal allograft recipient and was correlated to NAG. We found that oral 10 and 20 mg/kg/day Cy A produced no tubular toxicity nor drop in CC while 40 mg/kg doses resulted in a significant increase in Cr. with tubular vacuolation of low score in 33% of rats. On the other hand, higher doses of 80 mg/kg/day of Cy A produced tubular vacuolation of higher score in 83% of rats. A positive correlation was found between plasma K and Cy A doses. NAG was found to be elevated significantly before the appearance of definite pathogenic changes starting from 20 mg/kg/day. A strong positive correlation was observed between NAG and different doses of Cy A. Cy A trough level was found neither to be correlated to tubular toxicity nor to urinary NAG level. NAG was found to be increased in vast majority of renal allograft recipient on Cy A therapy with no correlation to either Cy A trough level or CyA dose. We can conclude that urinary NAG is superior to conventional methods used to diagnose acute Cy A toxicity as they appear in the urine before any pathological changes become evident. It is of no diagnostic value in chronic Cy A nephrotoxicity.